Doctor–patient communication about existential, spiritual and religious needs in chronic pain: A systematic review. (November 2019) - Andersen, Aida Hougaard; Assing Hvidt, Elisabeth; Hvidt, Niels Christian; Roessler, Kirsten K
Research documents that many chronic non-malignant pain patients experience existential, spiritual and religious needs; however, research knowledge is missing on if and how physicians approach these needs. We conducted a systematic review to explore the extent to which physicians address these needs in their communication with chronic non-malignant pain patients and to explore the facilitators and challenges of this communication. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, searching Embase, Medline, Scopus and PsycINFO. The quality of the included articles was assessed based on design-specific screening tools. We included four of 2337 screened articles and found the quality to be good. Physicians' communication about existential, spiritual and religious needs was given low priority and depended on the patients' own initiative, except when clinicians were interested in holistic care. Patient dissatisfaction with the physician's attention to these needs was related to higher pain and depression. Physicians' challenges for addressing these needs were their tendency to prioritize physiological aspects and close further elaboration of existential needs when addressed by the patients. The main facilitator was the individual physician's willingness to listen with openness and empathy to the patients' existential concerns. A tentative conclusion is that physicians rarely meet the existential, spiritual and religious needs of their chronic non-malignant pain patients. This might be due to higher priority of physical aspects, lack of time and a lack of knowledge about the importance of and training in the ability to address these needs. Further research is needed on physicians' communication about existential, spiritual and religious needs and on their training in here.